Integrated physiological and transcriptomic analysis uncovers the mechanism of moderate nitrogen application on promoting the growth and (-)-borneol accumulation of Blumea balsamifera - Yuan, Yuan; Tang, Wei-Jie; Cao, Jia-Yuan; Zhong, Ke; Mo, Ze-Jun; Zhou, Ying; Pang, Yu-Xin (Frontiers in Plant Science, 2025)
IntroductionBlumea balsamifera, a half-woody plant belonging to the Asteraceae family, is valued as both a medicinal and industrial crop primarily for its phytochemical component, (-)-borneol. Nitrogen (N) is essential for regulating the growth of B. balsamifera and the biosynthesis of (-)-borneol; however, the molecular mechanisms by which N influences these processes remain inadequately understood. This study aimed to elucidate the effects of N on growth and (-)-borneol synthesis at the molecular level.MethodsA field experiment was conducted in which B. balsamifera plants were fertilized with three different nitrogen regimes: 0 kg N ha-1 (control, CK), 150 kg N ha-1 (N1 treatment), and 300 kg N ha-1 (N2 treatment). Physiological and biochemical assessments were performed to evaluate the growth and metabolic responses of the plants under these varying N conditions. Additionally, transcriptome sequencing of leaves of B. balsamifera was conducted to elucidate the underlying molecular mechanisms involved.Results and discussionThe results indicated that both the N1 and N2 treatments significantly promoted the growth of B. balsamifera, with the 150 kg N ha-1 treatment (N1) resulting in the most favorable effects. Under the N1 treatment, the leaves harvested in October, November, and December exhibited the highest accumulation of (-)-borneol, with yields of 782 mg plant-1, 1102 mg plant-1, and 1774 mg plant-1, respectively, which were significantly different from those observed in the CK and N2 treatments. Comparative transcriptome analysis revealed a total of 6,714 differentially expressed genes (DEGs). Notably, several DEGs associated with auxin signaling and N metabolism were upregulated in the N1 and N2 treatments. In contrast, many DEGs related to carbohydrate metabolism, terpenoid backbone biosynthesis, monoterpenoid biosynthesis, and flavonoid biosynthesis were significantly upregulated in the CK treatment. Moreover, potential transcription factors (TFs) that may link N nutrition with the synthesis of medicinal components were identified. Our study demonstrates that N can enhance the accumulation of (-)-borneol in B. balsamifera when applied in appropriate quantities. These findings provide a comprehensive understanding of the relationship between N nutrition and (-)-borneol yield in B. balsamifera, offering valuable insights for future cultivation practices.